2018
DOI: 10.31458/iejes.442593
|View full text |Cite
|
Sign up to set email alerts
|

Application of Career Education in National Curriculum of Pakistan at Elementary Level

Abstract: This article intends to highlight the need and importance of career education in National Curriculum at an elementary Level. A case of Pakistan has been selected for this review. Applicability of career education in national curriculum has been discussed through extensive review of the National Education Policy (Ministry of Education Government of Pakistan, 2009) and career development framework practicing globally. Review has shown that there is need of career education in national curriculum at an elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The study found that teachers' knowledge and understanding of assessment improved as a result of using the framework and that there was a greater emphasis on formative assessment to support student learning. Similarly, a study by Khan and Zahid (2021) found that APF 2019 improved the validity, reliability, and quality of feedback provided to students.…”
Section: Effectiveness Of Apf 2019mentioning
confidence: 91%
“…The study found that teachers' knowledge and understanding of assessment improved as a result of using the framework and that there was a greater emphasis on formative assessment to support student learning. Similarly, a study by Khan and Zahid (2021) found that APF 2019 improved the validity, reliability, and quality of feedback provided to students.…”
Section: Effectiveness Of Apf 2019mentioning
confidence: 91%
“…Career education is increasingly recognized as an important transitional mechanism for young people (Keele et al, 2020). Khan (2018) emphasizes the importance of career education in the national school curriculum. To successfully integrate career education into mainstream academic content, teachers should receive career development training (Welde et al, 2015).…”
Section: Introductionmentioning
confidence: 99%